2012
DOI: 10.1667/rr2866.1
|View full text |Cite
|
Sign up to set email alerts
|

Decorporation Approach Following Rat Lung Contamination with a Moderately Soluble Compound of Plutonium Using Local and Systemic Ca-DTPA Combined Chelation

Abstract: Decorporation efficacy of prompt pulmonary delivery of DTPA dry powder was assessed following lung contamination with plutonium nitrate and compared to an intravenous injection of DTPA solution and a combined administration of both DTPA compounds. In addition, efficacy of a delayed treatment was assessed. In case of either early or late administration, insufflated DTPA was more efficient than intravenously injected DTPA in reducing the plutonium lung burden due to its high local concentration. Prompt treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…Optimization of the spray-drying conditions resulted in about 56% of the powder deposited in the lungs and 27% in the alveoli upon inhalation. 113 administration of this powder to rats contaminated with inhaled, poorly soluble pu oxide aerosols promoted as much plutonium removal as intravenous Dtpa, 114 warranting further safety and efficacy studies that would confirm the viability of this new formulation as an emergency treatment.…”
Section: Pharmaceutical Approachesmentioning
confidence: 96%
“…Optimization of the spray-drying conditions resulted in about 56% of the powder deposited in the lungs and 27% in the alveoli upon inhalation. 113 administration of this powder to rats contaminated with inhaled, poorly soluble pu oxide aerosols promoted as much plutonium removal as intravenous Dtpa, 114 warranting further safety and efficacy studies that would confirm the viability of this new formulation as an emergency treatment.…”
Section: Pharmaceutical Approachesmentioning
confidence: 96%
“…DTPA is effective at chelating and removing plutonium from the body when the radionuclide exists in the blood and extracellular fluids of soft tissues or that is loosely bound on skeletal surfaces (Breustedt et al 2009;Durbin et al, 1998;Fritsch et al 2010). Studies have indicated that liver and skeleton decorporation is evident in animals and humans (Bhattaracharyya et al 1978a and b;Cohen et al 1974;Fritsch et al 2010;Gremy et al 2012;Phan et al 2004;Roedler et al 1989). DTPA is able to chelate monomeric plutonium in the presence of competing endogenous proteins, such as transferrin, but it has a much lower affinity than bone proteins for monomeric plutonium Taylor 1970, 1972;Durbin et al 1998).…”
Section: Chelationmentioning
confidence: 99%
“…Observed skeletal decorporation is likely due to removing plutonium from other organs and tissues. Depending on treatment protocol, DTPA administered by multiple daily treatments, intramuscular injection or nebulizer was proven to be more effective than by a single intravenous injection due to DTPA having a short residence time once it reaches the blood stream with a clearance half-time of 20 min (Durbin and Schmidt 1989;Gremy et al 2010Gremy et al , 2012Stather et al 1983;Volf 1974). The Ca-DTPA complex is initially more effective than Zn-DTPA for chelating plutonium, but due to the toxicity of Ca-DTPA, continued use is discouraged after the initial treatment (Durbin et al 1998;Gemenetzis and Volf 1977;IAEA 1978).…”
Section: Chelationmentioning
confidence: 99%
“…Inhalation of the aerosolized DTPA solution is only recommended in cases of contamination by inhalation (Food and Drug Administration, 2003;ANSM, 2011). Experimental DTPA formulations have also been tested in rodents such as liposomes for cell entry enhancement (Grémy et al, 2018) or a dry powder for better delivery into deep lung (Grémy et al, 2010;Grémy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%